1996
DOI: 10.1126/science.272.5266.1300
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rotation and Dynamics of the Solar Interior

Abstract: Splitting of the sun's global oscillation frequencies by large-scale flows can be used to investigate how rotation varies with radius and latitude within the solar interior. The nearly uninterrupted observations by the Global Oscillation Network Group (GONG) yield oscillation power spectra with high duty cycles and high signal-to-noise ratios. Frequency splittings derived from GONG observations confirm that the variation of rotation rate with latitude seen at the surface carries through much of the convection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
231
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 373 publications
(237 citation statements)
references
References 71 publications
6
231
0
Order By: Relevance
“…Helioseismic results from Thompson et al (1996) and Schou et al (1998) showed that radial gradients in subsurface angular velocity are small in the convection zone down to around 0.7 solar radii, and that the large radial shears that occur around 0.7 solar radii are such that the rotation rate decreases with depth at low latitudes, contrary to the assumption of Leighton (1969). Unlike the model of Leighton (1969), the model behaved in a stable, oscillatory manner without a radial gradient in the interior angular velocity.…”
Section: The Influence Of Meridional Flows On the Babcock-leighton Modelmentioning
confidence: 49%
“…Helioseismic results from Thompson et al (1996) and Schou et al (1998) showed that radial gradients in subsurface angular velocity are small in the convection zone down to around 0.7 solar radii, and that the large radial shears that occur around 0.7 solar radii are such that the rotation rate decreases with depth at low latitudes, contrary to the assumption of Leighton (1969). Unlike the model of Leighton (1969), the model behaved in a stable, oscillatory manner without a radial gradient in the interior angular velocity.…”
Section: The Influence Of Meridional Flows On the Babcock-leighton Modelmentioning
confidence: 49%
“…Surface differential rotation (SDR) can be easily observed in the Sun, with detailed observations going back to Carrington (1860); and subsurface rotation has been inferred from helioseismic data of the Sun's 5 minute p-mode oscillations (e.g., Thompson et al 1996). However, it is a challenge to observe SDR directly at the surfaces of other stars.…”
Section: Introductionmentioning
confidence: 99%
“…The flow structures of both scales can deepen our understanding of the generation of solar magnetism, and of the birth and evolution of solar active regions. Solar rotation rates have been widely studied by use of direct Doppler velocity measurements (e.g., Howard & LaBonte 1980), by tracking photospheric magnetic or supergranular features (e.g., Meunier 1999), and by both global and local helioseismology (e.g., Thompson et al 1996;Giles 1999). The solar-cycle variations of solar rotation known as torsional oscillations were first observed by Howard & LaBonte (1980), and then studied by many researchers using different approaches (e.g., Snodgrass 1985;Howe et al 2000;Ulrich 2001).…”
Section: Introductionmentioning
confidence: 99%